The magnitude of ivacaftor effects on fluid secretion via R117H-CFTR channels: Human in vivo measurements. - Jessica E Char; Colleen Dunn; Zoe Davies; Carlos Milla; Richard B Moss; Jeffrey J Wine (PLoS ONE)
We optically measured effects of orally available ivacaftor (Kalydeco®) on sweat rates of identified glands in 3 R117H subjects, each having a unique set of additional mutations, and compared them with 5 healthy control subjects tested contemporaneously. We injected β-adrenergic agonists intradermally to stimulate CFTR-dependent 'C-sweat' and methacholine to stimulate 'M-sweat', which persists in CF subjects. We focused on an R117H-7T/F508del subject who produced quantifiable C-sweat off ivacaftor and was available for 1 blinded, 3 off ivacaftor, and 3 on ivacaftor tests, allowing us to estimate in vivo fold-increase in sweat rates produced by ivacaftor's effect on the open probability (PO) of R117H-CFTR. Measured sweat rates must be corrected for sweat losses. With estimated sweat losses of 0.023 to 0.08 nl·gland-1·min-1, ivacaftor increased the average C-sweat rates 3-7 fold, and estimated function as % of WT were 4.1-12% off ivacaftor and 21.9-32% on ivacaftor (larger values reflect increased loss estimates). Based on single tests, an R117H-7T/ R117H-7T subject showed 6-9% WT function off ivacaftor and 28-43% on ivacaftor. Repeat testing of an R117H-5T/F508del subject detected only trace responding to ivacaftor. We conclude that in vivo, R117H PO is strongly increased by ivacaftor, but channel number, mainly determined by variable deletion of exon 10, has a marked influence on outcomes.